The sustainability of shared mobility in London: the dilemma for governance - Akyelken, N; Banister, D; Givoni, M (MDPI, 2018)
The role of governments in the regulation of potentially beneficial low carbon practices, such as car sharing, has proved difficult, as there are many different actors involved and as existing practices can be undermined. The mobility sector provides clear evidence of these dilemmas, as a wide range of users need to be engaged in the discourse over the innovations, and as existing governance structures may be unsuitable for addressing both the opportunities and limitations of innovation. This paper focuses on the sustainability implications of shared mobility and the need for new approaches to governance. A qualitative study of car sharing in London is used to examine the ideas, incentives, and institutions of the key actors involved in this sharing sector. The elements of change and continuity in the emerging sharing economy indicate the different possibilities for enhancing sustainable mobility. Any search for an alternative governance regime should take account of the ideational factors that would require an understanding of the different incentives needed to accommodate the full range of actors involved with the sharing economy.